Resource use efficiency of indoor lettuce (Lactuca sativa L.) cultivation as affected by red:blue ratio provided by LED lighting - Pennisi, Giuseppina; Orsini, Francesco; Blasioli, Sonia; Cellini, Antonio; Crepaldi, Andrea; Braschi, Ilaria; Spinelli, Francesco; Nicola, Silvana; Fernandez, Juan A.; Stanghellini, Cecilia; Gianquinto, Giorgio; Marcelis, Leo F. M. (Scientific reports, 2019)
LED lighting in indoor farming systems allows to modulate the spectrum to fit plant needs. Red (R) and blue (B) lights are often used, being highly active for photosynthesis. The effect of R and B spectral components on lettuce plant physiology and biochemistry and resource use efficiency were studied. Five red:blue (RB) ratios (0.5-1-2-3-4) supplied by LED and a fluorescent control (RB = 1) were tested in six experiments in controlled conditions (PPFD = 215 μmol m −2 s −1 , daylength 16 h). LED lighting increased yield (1.6 folds) and energy use efficiency (2.8 folds) as compared with fluorescent lamps. Adoption of RB = 3 maximised yield (by 2 folds as compared with RB = 0.5), also increasing leaf chlorophyll and flavonoids concentrations and the uptake of nitrogen, phosphorus, potassium and magnesium. As the red portion of the spectrum increased, photosystem II quantum efficiency decreased but transpiration decreased more rapidly, resulting in increased water use efficiency up to RB = 3 (75 g FW L −1 H 2 O). The transpiration decrease was accompanied by lower stomatal conductance, which was associated to lower stomatal density, despite an increased stomatal size. Both energy and land surface use efficiency were highest at RB ≥ 3. We hereby suggest a RB ratio of 3 for sustainable indoor lettuce cultivation.